A Structural Model of Teacher Self-Efficacy, Emotion Regulation, and Psychological Wellbeing Among English Teachers - Xiyun, Shen; Fathi, Jalil; Shirbagi, Naser; Mohammaddokht, Farnoosh (Frontiers in Psychology, 2022)
Because of the exacting nature of teaching, identifying factors affecting teachers’ mental health and psychological well-being are of paramount importance. Parallel with this line of inquiry, the goal of this project was to test a model of psychological well-being based on teacher self-efficacy and emotion regulation in an EFL context. To this end, 276 Iranian English teachers participated in this survey. First, the measurement models for the three latent constructs were verified through performing Confirmatory Factor Analysis (CFA). Then Structural Equation Modeling (SEM) was used to test the hypothesized model. SEM outcomes evince that both teacher self-efficacy and emotion regulation were the significant predictors of teachers’ psychological well-being, with teacher self-efficacy being a stronger correlate than emotion regulation. The findings offer significant implications for English as a Foreign Language (EFL) teachers.